2018
DOI: 10.1177/0020764018789200
|View full text |Cite
|
Sign up to set email alerts
|

Stigma associated with mental illness and its treatment in the Arab culture: A systematic review

Abstract: A large diversity in the stigmatizing beliefs, actions and attitudes toward treatment of mental illness within the Arab population were identified. The influence of cultural variations on stigma should be explored further and used to tailor anti-stigma interventions in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
141
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(168 citation statements)
references
References 64 publications
16
141
2
1
Order By: Relevance
“…Most of the research about stigmatization in the medical field in Arabic countries was related to mental health. 14,15 We previously clearly confirmed that the visibility of the skin lesions is a key factor for stigmatization experience and, as we have already emphasized, proper stigmatization assessment in dermatological patients would contribute to the entire, complete understanding of their suffering and would facilitate the holistic therapeutic approach. 6 Therefore, the creation of Arabic-language instruments to assess skin-related stigmatization level was crucial for daily clinical practice and for the future research in this field.…”
Section: Discussionsupporting
confidence: 58%
“…Most of the research about stigmatization in the medical field in Arabic countries was related to mental health. 14,15 We previously clearly confirmed that the visibility of the skin lesions is a key factor for stigmatization experience and, as we have already emphasized, proper stigmatization assessment in dermatological patients would contribute to the entire, complete understanding of their suffering and would facilitate the holistic therapeutic approach. 6 Therefore, the creation of Arabic-language instruments to assess skin-related stigmatization level was crucial for daily clinical practice and for the future research in this field.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, stigma has been proven to have negative effects on individuals’ self‐esteem, family relationships, educational and job opportunities. Individuals suffering from mental disorders mostly face two challenges in coping with their disorders: one relating to the symptoms of the mental disorders and another related to the stigmatization of their problem (Chen, Sargent, & Stuart, 2018; Heath, Brenner, Lannin, & Vogel, 2018; Shechtman, Vogel, Strass, & Heath, 2018; Stuart, Sartorius, & Thornicroft, 2019; Zolezzi, Alamri, Shaar, & Rainkie, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, attempts aiming to decrease imposed mental health difficulties among youth in the Middle East have accelerated (Pampati et al, 2018; Sijbrandij et al, 2017). In parallel, studies on attitudes and beliefs associated with psychiatric issues, especially related to children and adolescents, have been considered by several social science and health researchers in the Middle East (Alrahili, Almatham, Bin Haamed, & Ghaziuddin, 2016; Morawska & Sultan, 2016; Sewilam et al, 2015; Zolezzi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations